Using Augmented Reality Prototypes in Design Education - Chandrasekera, Tilanka (Design and Technology Education: An International Journal, 2014)
Prototyping or model making in the Architectural and Interior Design process is an established method of design problem solving. By using prototypes, design students can better visualize structures and can give students a more concrete result when working on a design project. According to a study by Grosslight, Unger, Jay and Smith (1991), students are likely to think of prototypes as physical copies of reality that envelop various spatiotemporal views, instead of representations that envelop various theoretical perspectives. Past literature and research has suggests that student’s rate building prototypes highly when compared with other types of representations, which implies that they are better able to learn the design process when using prototypes (Lemons, Carberry, Swan & Rogers, 2010). This study documents alternate modeling strategies utilizing technologies such as Virtual Reality (VR) and Augmented Reality (AR) in Architectural and Interior Design education through the Technology Acceptance Model to better understand how students perceive design solutions in early design studios. The results of the study suggest that design students found physical models to be comparable to AR models and that the AR technology was easy to use.